Factors associated with family caregiver dissatisfaction with acute hospital care of older cognitively impaired relatives - Whittamore, Katherine H.; Goldberg, Sarah E.; Bradshaw, Lucy E.; Harwood, Rowan H. (Wiley, 2014)
Objectives To identify patient and caregiver characteristics associated with caregiver dissatisfaction with hospital care of cognitively impaired elderly adults. Design Secondary analysis of data from a randomized controlled trial. Setting An 1,800-bed general hospital in England providing the only emergency medical services in its area. Participants Cognitively impaired individuals aged 65 and older randomly assigned to a specialist unit or standard geriatric or internal medical wards (N = 600) and related caregivers (N = 488). Measurements Patient and caregiver health status was measured at baseline, including delirium, cognitive impairment, behavioral and psychological symptoms, activities of daily living, and caregiver strain. Caregiver satisfaction with quality of care was ascertained after hospital discharge or death. Results Four hundred sixty-two caregivers completed satisfaction questionnaires. Regardless of assignment, 54% of caregivers were dissatisfied with some aspects of care, but overall 87% were satisfied with care. The main areas of dissatisfaction were communication, discharge planning, and medical management. Dissatisfaction was associated with high levels of patient behavioral and psychological symptoms on admission, caregiver strain and poor psychological well-being at admission, a diagnosis of delirium, and the relationship between the caregiver and the patient. There was less dissatisfaction from caregivers of patients managed on the specialist Medical and Mental Health Unit than those on standard wards, after controlling for multiple factors. Conclusion Dissatisfaction was associated with patient behavioral and psychological symptoms and caregiver strain but was not immutable to efforts to improve care.